Inovasi Desa Riset Kesongo: Pemanfaatan sampah rumah tangga untuk produksi pupuk organik berkualitas - Ismawati, Tri Retno; Ziadaturrahmah, Ziadaturrahmah; Hapsari, Itsna; Hanandita, Dah Tiara; Mahasyin, Muhammad Alifudin Nawal; Suryanto, Suryanto (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Composting is one of the various methods of processing household waste that aims to reduce and also change the composition of waste into useful products. This article tries to provide an overview and explanation related to the organic fertilizer production work program, including the process, stages, results, and benefits. This article was written using a qualitative approach with a participatory observation approach. As a result, the UIN Salatiga 2024 KKN Team has gained new understanding and insights in terms of utilizing household waste, in addition, the KKN team also succeeded in following the manufacture of the fertilizer from the stage of collecting raw materials, then carrying out fermentation, to the grinding and refining process of the fertilizer, and ending with the creation of a planting medium by the KKN team. This article is limited to the implementation of KKN which is integrated with the KKN Period July-August 2024.